Interpretations of Heamatological Parameters in COVID-19 Patients with Diabetic Mellitus Comorbidity - Zia-ur-Rehman Farooqi; Nimra Shaheen; Umair Waqas; Abid Ali; Waqar Mehmood Dar (Current Trends in OMICS, 2022)
Coronaviruses (CoVs) can infect a wide range of wild and domestic hosts including animals, avian, mammals, rodents, and human beings. COVID infection has already been reported in whales, bats, mice, birds, and giraffes,s and infection to domestic and life stock cause heavy losses to the economy. These viruses cause mild to severe respiratory, enteric, and systemic infections. Worldwide 525,268,297 (May 19, 2022) individuals have been infected since the first case of COVID-19 was reported in Wuhan China with 6,295,402 deaths (May 19, 2022). In Pakistan, a total of 1,529,560 cases of COVID-19 have been reported with 30,379 deaths (May 19, 2022). Province wise data reported 577,201 cases in Sindh, 219,616 in KPK, 506,865 in Punjab, 135,312 in Islamabad, 35,494 in Baluchistan, and 43,324/11,748 in AJK/GB. This study evaluated the hematological parameters in diabetic patients affected by COVID-19. This cross-sectional retrospective study was conducted at the Department of Pathology, Aziz Bhatti Shaheed Hospital, Gujrat, Pakistan. Data were collected from a total of 111 patients of COVID-19 with DM comorbidities and analyzed for the comparison of Leukocytes parameters, platelets count, Red Blood Cell (RBC) counts, and their indices Packed Cell Volume (PCV), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC)] with their reference values. The mean RBC count was 4.45 with SD (±0.84). The data also showed the mean of Hemoglobin (Hb) level as 12.45 g/dl (SD ±3.01), PCV as 36.06 (SD ±9.16), MCV as 81.86 (SD ±7.32), MCH as 29.05 (SD ±6.27), and MCHC as 32.61 (SD ±3.65). A comparison was also made between male and female COVID-19-enrolled patients for hematological associated changes in DM. The frequency distribution of leukocytes and thrombocytes showed lymphocytosis and thrombocytopenia.  It was Concluded that hematological parameters are important in monitoring disease severity, progression, and management in COVID-19 patients with diabetes comorbidity.